2018
DOI: 10.19126/suje.321775
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Classroom Incivility Scale into Turkish

Abstract: Öz. Araştırmanın amacı Farrell vd. (2016) tarafından geliştirilen Sınıf İçi Kaba Davranışlar Ölçeği'nin Türkçe'ye uyarlanmasıdır. Dil geçerliği için İngilizce ve Türkçe ölçekler uygulanmış olup, maddeler arasında korelasyon analizi yapılmıştır. Ölçeğin yapı geçerliğini belirlemek için Acimlayıcı Faktör Analizi (AFA) yapılmıştır. Araştırmanın örneklem büyüklüğü ve faktör analizi yapılabilmesi uygunluğu için KMO .816 ve Barlett testi χ2 değeri 611,482 (p<.001) olarak bulunmuştur. Ölçeğin yapı geçerliliği incelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In recent years, research exploring classroom incivility has garnered increasing attention (e.g., Spadafora et al, 2020; Bingöl et al, 2018; Katt et al, 2018; Volk et al, 2016). Incivility is defined as rude or disrespectful behavior that violates social norms and has an unclear motivation (Andersson & Pearson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research exploring classroom incivility has garnered increasing attention (e.g., Spadafora et al, 2020; Bingöl et al, 2018; Katt et al, 2018; Volk et al, 2016). Incivility is defined as rude or disrespectful behavior that violates social norms and has an unclear motivation (Andersson & Pearson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the pedagogical aspect of those reactions has not been discussed sufficiently. It is observed that teachers exhibit their reactions depending on the situation and regardless of their pedagogical aspects (Bingöl, et al, 2018). This indicates that the pedagogical aspect of the reactions is neglected when preventing undesirable behaviors.…”
Section: Kaynakçamentioning
confidence: 99%
“…Adolescent classroom incivility has begun to gain attention globally in recent research (Bіngӧl et al, 2018; Kinoshita & Sato, 2022; Nugroho et al, 2020; Spadafora et al, 2022; Susilawati, et al, 2020). Adolescent research has suggested that uncivil behavior in the classroom may not only disrupt classroom learning but may also have negative effects on the perpetrator.…”
Section: Introductionmentioning
confidence: 99%